The Analysis of Minimum Distribution to Each Mustahiq and Its Relevance to Zakat al-Fitr Obligation to All Muslims - Muhammad Nurul Alim (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to analyze the minimum needs of Zakat al-Fitr distributed to Mustahiq so they do not beg on Eid al-Fitr and can pay Zakat al-fitr. Being Muslims, fuqaraa and masakeen as priority recipients of Zakat al-Fitr are also obliged to pay Zakat for themselves. This study employs exploratory and normative legal research methodology that examines the library’s source as legal material that becomes a means of analysis. The finding result of this study suggests that the minimum need of Zakat al-Fitr distributed to each recipient is 2 sha of which 1 sha to Eid al-Fitr food and the other one sha to be repaid as their Zakat al-fitr. If Zakat al-Fitr is distributed in the form of money, then the distributed amount is equivalent to the price of 2 sha of local staple food. Sociological impact of such distribution is that all Muslims in areas where Zakat al-Fitr is collected can pay Zakat. The practical implication of this study is to distribute Zakat al-Fitr to each recipient as much as 2 sha and to raise the recipients' awareness of their obligation to pay Zakat al-Fitr for themselves and their dependents from the staple food or money they received.